CHRONIC HEART FAILURE IN PATIENTS WITH HYPERTROPHIC CARDIOMYOPATHY - N. S. Krylova; E. V. Avdeeva; N. G. Poteshkina (Российский кардиологический журнал)
In total, 86 patients with hypertrophic cardiomyopathy (HCMP), aged 21-88 years, were examined. All participants were divided into two groups: Group I – patients without signs and symptoms of chronic heart failure (CHF); Group II – patients with Stage IIB CHF. There are three pathophysiological mechanisms of CHF development in HCMP: – concentric left ventricular (LV) hypertrophy with minimal LV chamber size, diastolic LF dysfunction and systolic right ventricular (RV) dysfunction; – LV remodelling and dilatation, systolic LV dysfunction; – persistent atrial fibrillation. The HCMP clinical course, characterized by congestive heart failure and fatal outcome, was more prevalent in women. In our patients, LV outflow obstruction did not affect CHF development.